Eficiencia de la semilla de moringa (Moringa oleífera) en la remoción de sólidos suspendidos totales en Aguas. - Montesdeoca Loor, Henry Gabriel (2018)
The objective of this research was to evaluate the efficiency of moringa seed (M. oleifera) in the removal of total suspended solids (TSS) in waters. For this, seeds were collected at their optimum stage of maturity. These were pulverized by a mill to be sieved and obtain flour. Subsequently, by means of a saline extraction process, the polyelectrolyte that makes up the crude saline extract of the moringa seed was obtained. A completely randomized design (3x2) was applied for the dose determination in which high doses (4 ml) of medium (2 ml) and low (0.5 ml) of flour, polyelectrolyte and aluminum sulphate were prepared (control), all at a concentration of 5%, and with 3 replications for each treatment. Finally, as a result of the best treatment, a 98% efficiency in the removal of SST in the water was obtained favoring the 0.5 ml dose of the polyelectrolyte of the moringa seed, surpassing 94.8% of the same dose of the aluminum sulphate, based on the application of the ANOVA table (Infostat software), thus promoting the use of an alternative of natural origin with a sustainable approach in the industrial sector where large quantities of wastewater are generated.